SPLOR-T : an interactive urban spatiotemporal data exploration web approach (2019)
"The analysis of spatio-temporal urban data has evolved along the last 30 years. Data heterogeneity and segmented analysis is a frequent issue in this context. We present a new proposal to address these challenges by using the visual analytics approach in a web environment using the "What-Where-When" pyramidal paradigm to drive the analysis. Thanks to the flexibility of new web tools, we arrive to offer with S-PLOR-T a flexible and multi-screen web interface. Furthermore, we provide an architecture to allow to put coordinated visualizations, letting an analyst to have a clear notion of its data through interactions within the three main "Wh*" dimensions. With S-PLOR-T, the users will result in a customizable analysis in order to support the finding of new insights and support an effortless decision making with them. Additionally, our approach allows the user, not only to visual query any view, but to explore and to analyze multi-scale attributes within the space and the time. In this paper, we present a use case which was built and tested with domain experts in land use and mobility."--Tomado del Formato de Documento de Grado.